Integrative functional genomics identifies regulatory mechanisms at coronary artery disease loci - Clint L. Miller (Nature Portfolio, 2016)
Coronary heart disease is the leading cause of death worldwide with multiple environmental and genetic risk factors. Here the authors integrate genomic, epigenomic and transcriptomic mapping to elucidate causal variation and mechanisms of known genetic associations.